Non-Sexual Violence Values in Academic Culture of Universities in Indonesia - Azizatuz Zahro; Ritha Dalimunthe; Evi Feronika Elbaar; Desinta Dwi Rapita (Randwick International of Social Science Journal, 2023)
Sexual violence that happens in Indonesian universities is often considered trivial and receive little attention. Universities that are healthy, comfortable, safe, and free from sexual violence will ensure the continuity of educational activities. Colleges or universities should be a place for students to gain knowledge and improve morale. This article focuses on describing the non-sexual violence values developed by universities in their academic culture. This qualitative research was conducted at Universitas Negeri Malang (UM), Universitas Sumatera Utara (USU) and Universitas Palangkaraya (UPR). Data was collected through surveys, in-depth interviews, focus group discussions (FGD), secondary data review, and observation. The results of the study showed that universities have developed non-sexual values ​​by strengthening the governance of higher education institutions and the culture of the community of students, educators, and educational staff.